Resilient high-rise property? Grenfell Tower and beyond - Bright, SJ (Association for Law, Property & Society, 2023)
In June 2017, the tragic fire at Grenfell Tower, London, led to the loss of seventy-two lives. Since then thousands of blocks of flats in England have been discovered to have life-critical safety failures. In England, flats are owned on a long leasehold basis, and this Article explains the devastating impact that this building safety crisis continues to have on leaseholders and residents in affected blocks. This has triggered a “property moment” that brings to the fore questions about the state’s role in shaping property. The Article sets out the surprising interventions in both property law and private law implemented through the Building Safety Act 2022 and how they disrupt established norms. This includes complex provisions that override lease terms to provide (some) leaseholders with protection from remediation costs. Throughout this Article, the lens of resilience is adopted to reflect on the many understandings of property—as real estate, as a form of ownership, as home, as investment, and as a legal institution. It is argued that the 2022 Act reveals the adaptive resilience of the legal institution of property, and that property laws must be further adapted to meet contemporary challenges of aging structures and net-zero.